Analisis SWOT Dalam Menentukan Strategi Pemasaran Untuk Meningkatkan Minat Beli Konsumen (Studi Kasus Pada CC-Mart Sotabar-Pasean) - Ach Taufiqurrahman; Eka Farida; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study's objectives are as follows: 1) Determine whether CC-Mart Sotabar-Pasean's marketing strategy and SWOT analysis can increase customer interest in purchasing, and 2) Determine whether CC-Mart Sotabar-Pasean's marketing strategy can be determined by SWOT analysis. 3) To learn how the marketing strategy used by CC-Mart Sotabar-Pasean was put into action. Qualitative research was used for this study. Techniques for gathering data include conducting interviews, observing employees, and customers of CC-Mart Sotabar-Pasean, as well as documenting those interactions. The SWOT matrix, IFE and EFE matrices, and SWOT diagrams are utilized in this study's data analysis. The study's SWOT analysis identified both internal and external factors, with the position of strength (strength) receiving a higher overall score of 3.65 and the position of weakness (weakness) receiving a score of 1.31. However, the company's position of opportunities (opportunities) on the external factors is greater than its position of threats (threats) with a score of 1.67. Because CC-Mart Sotabar-Pasean is in quadrant I, which is a profitable position, the implementation of the strategy employs an aggressive growth strategy (Growt Oriented Strategy), according to the calculations from the analysis. CC-Mart Sotabar-Pasean makes use of its advantages and opportunities. so that CC-Mart Sotabar-Pasean can survive and compete with its rivals using this strategy. Keywords : Marketing strategy, SWOT analysis, and consumer interest in purchasing.